Pengaruh Latihan Catching Terhadap Kecepatan Reaksi Kiper Futsal Di Ekstrakulikuler SMP YAKHA Garut - Salamudin, Rizki; Hermawan, Irwan; Sonjaya, Azhar Ramadhana (Jurnal Porkes, 2025)
This study aims to determine the impact of catching training on increasing the reaction speed of futsal goalkeepers. The method used was an experiment with a pretest-posttest design. The population of this study was futsal goalkeepers at a local club, and the sample used consisted of 10 futsal goalkeepers who were selected purposively. The instrument used to collect data was a reaction speed test. The data analysis technique used was descriptive analysis and t-test to compare pretest and posttest results. The results showed that there was a significant increase in the reaction speed of futsal goalkeepers after participating in the catching training program, with an average pretest result of 37.14 and posttest of 72.86. the average score of goalkeeper reaction speed was 37.14, with the lowest score of 20 and the highest of 60. Comparison of the average between pretest and posttest showed a difference of 35.72 points. there was a significant increase of 35.72 points in the average reaction speed ability of goalkeepers after being given treatment. The conclusion of this study is that catching exercises can significantly improve the reaction speed of futsal goalkeepers. Therefore, this exercise is recommended to be applied in the routine training program of futsal goalkeepers to improve their performance in matches.